PTU-212 A systematic review of bioabsorbable synthetic anal fistula plug for treatment of cryptoglandular fistula in ano. (22nd June 2015) - Narang, SK; Jones, C; Alam, N; Pathak, S; Daniels, I; Smart, N
Abstract : Introduction: Damage to the anal sphincter musculature during treatment of fistula in ano is a dreaded complication. Absorbable synthetic fistula plug have been used as a novel sphincter saving technique. The aim of this systematic review was to review the literature and assess the effectiveness of absorbable synthetic fistula plug for treatment of cryptoglandular fistula in ano. Method: A systematic review of all English language literature relevant to fistula plug treatment of cryptoglandular fistula in ano, published between 1 January 2010 and 15 February 2015 was carried out using MEDLINE, EMBASE and the Cochrane Library of Systematic Reviews/Controlled Trials for relevant literature. Relevant articles were identified, quality assessed using the MINORS criteria and the data were extracted by two researchers independently. The identified articles were assessed with regards to fistula healing rate, duration of follow up and complication rates related to the use of bioabsorbable fistula plugs. Results: A total of 26 potential articles were identified from the literature search. Using the predefined inclusion and exclusion criteria, 6 articles were included for the final analysis, data extraction and data synthesis. Of the 6 studies included in the review only 3 studies were prospective in study design. Complete data were available for 187 of the 221 patients who underwent this treatment. The age of the participants ranged from 19–82 years. The fistula healing rates were reported to be between 15.8% >72.7% on follow up ranging from 2–19 months. Early or delayed plug extrusion occurred in 16 patients. A slight deterioration in continence was reported in 11 patients. Conclusion: Synthetic bioabsorbable anal fistula plugs appears to be a simple and safe procedure associated with low complication rates and faecal incontinence. Given the significant heterogeneity in the study design, sample size and reported outcomes, further studies with longer follow up are needed. Disclosure of interest: None Declared.